2010
DOI: 10.1002/pon.1577
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care needs in patients with lung cancer

Abstract: Our findings suggest that lung cancer survivors have many unmet needs. Patients who report higher physical distress and intrusive stress symptoms, or lower satisfaction with their health care, may experience the highest level of supportive care need and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
151
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 45 publications
16
151
2
2
Order By: Relevance
“…The findings of this study not only validate the ongoing challenges of survivorship reported by studies in other oncological groups [24][25][26][42][43][44], but also are an important step towards understanding the problems with which a growing number of cancer survivors require assistance in the community. This information will assist in evidence-based planning and management and can improve clinical service delivery in identified areas for improved patient outcomes [26,45].…”
Section: Discussionsupporting
confidence: 68%
“…The findings of this study not only validate the ongoing challenges of survivorship reported by studies in other oncological groups [24][25][26][42][43][44], but also are an important step towards understanding the problems with which a growing number of cancer survivors require assistance in the community. This information will assist in evidence-based planning and management and can improve clinical service delivery in identified areas for improved patient outcomes [26,45].…”
Section: Discussionsupporting
confidence: 68%
“…33 A small literature suggests that lung cancer patients have significantly more unmet supportive care needs than any other cancer patients. [34][35][36] Results from a US study 36 demonstrates that a large majority of patients experience unmet supportive care needs across multiple domains and having unmet supportive care needs is associated with dissatisfaction with health care providers and mood disturbance. Sanders et al 36 suggest that efforts to improve the clinical assessment of supportive care needs could improve patient satisfaction with care and QoL outcomes in patients with lung cancer.…”
Section: Patient Symptomatologymentioning
confidence: 99%
“…2 They report having a number of distinct supportive care needs, including tasks of daily living and psychological needs. [3][4][5] Patients may benefit from methods and measures specific to assessing QOL at the end of life rather than to lung cancer as such. 6 Even when palliative treatment does not prolong survival in these patients, it can significantly ameliorate symptoms leading to improvements in QOL.…”
Section: Introductionmentioning
confidence: 99%